The role of biology in planetary evolution: cyanobacterial primary production in low‐oxygen Proterozoic oceans. (21st December 2015) - Hamilton, Trinity L.; Bryant, Donald A.; Macalady, Jennifer L.
Summary: Understanding the role of biology in planetary evolution remains an outstanding challenge to geobiologists. Progress towards unravelling this puzzle for Earth is hindered by the scarcity of well‐preserved rocks from the Archean (4.0 to 2.5 Gyr ago) and Proterozoic (2.5 to 0.5 Gyr ago) Eons. In addition, the microscopic life that dominated Earth's biota for most of its history left a poor fossil record, consisting primarily of lithified microbial mats, rare microbial body fossils and membrane‐derived hydrocarbon molecules that are still challenging to interpret. However, it is clear from the sulfur isotope record and other geochemical proxies that the production of oxygen or oxidizing power radically changed Earth's surface and atmosphere during the Proterozoic Eon, pushing it away from the more reducing conditions prevalent during the Archean. In addition to ancient rocks, our reconstruction of Earth's redox evolution is informed by our knowledge of biogeochemical cycles catalysed by extant biota. The emergence of oxygenic photosynthesis in ancient cyanobacteria represents one of the most impressive microbial innovations in Earth's history, and oxygenic photosynthesis is the largest source of O2 in the atmosphere today. Thus the study of microbial metabolisms and evolution provides an important link between extant biota and the clues from the geologic record. Here, we consider the physiology of cyanobacteria (the only microorganisms capable of oxygenic photosynthesis), their co‐occurrence with anoxygenic phototrophs in a variety of environments and their persistence in low‐oxygen environments, including in water columns as well as mats, throughout much of Earth's history. We examine insights gained from both the rock record and cyanobacteria presently living in early Earth analogue ecosystems and synthesize current knowledge of these ancient microbial mediators in planetary redox evolution. Our analysis supports the hypothesis that anoxygenic photosynthesis, including the activity of metabolically versatile cyanobacteria, played an important role in delaying the oxygenation of Earth's surface ocean during the Proterozoic Eon.